The Development of the Nursing–based Continuing Care Guideline for Stroke Survivors with the Participation of the Hua Hin Hospital Health Network - Noppakhun, Thichatthaya; Dechathonamorn, Suwatcharee; Sonti, Supreeya (Journal of Public Health Nursing, 2023)
This participatory action research aimed to assess stroke patient care and develop continuous nursing care guidelines for Hua Hin Hospital and its network. The research comprised three phases: 1) planning for change, involving studying the problems and barriers in providing continuous nursing care, assessing the knowledge of the general public and at-risk groups, conducting post-stroke patient interviews, and collaborating with researchers to develop care guidelines;2) implementing and observing the guidelines, assessing collaboration, clinical outcomes, and conducting home visits; and 3) reflecting and providing feedback by analyzing data from interviews, group discussions, assessments, and records. Qualitative data underwent content analysis, while quantitative data were analyzed using descriptive statistics. Findings revealed areas for improvement in stroke patient care, including 1) inadequate knowledge and skills in assessing symptoms and timely transfers, 2) limited experience in emergency patient transfers for stroke, 3) low awareness and understanding of stroke severity, and 4) inadequate integrated health services. Accordingly, the study proposes an action plan: 1) establishing a Community Stroke Team, 2) implementing the "Know Fast, Act Safe, Reduce Disability" campaign, and 3) providing continuous nursing care through Smart Discharge Planning, Smart Home Visit, and Smart Counselling. Process outcomes indicated participants' ability to assess symptoms, an average practice time of 196.25 minutes for patient transfers, and clear practice guidelines for healthcare providers and networks. Clinical outcomes showed emergency stroke patients received treatment within 210 minutes, and post-stroke patients receiving continuous nursing care had an 18.18% complication rate, effectively managed by the Community Stroke Team without rehospitalization. Reflections on the study highlighted that the developed guidelines facilitated role alignment and raised community awareness and self-care abilities. However, enhancing problem-solving skills within the Community Stroke Team is necessary. This participatory action research provided comprehensive insights into stroke patient care and practical recommendations for improving continuous nursing care. The collaborative research process ensured its relevance and applicability within the context of Hua Hin Hospital and its network.